El discurso del movimiento LGBTI en Ecuador: usos del lenguaje y la tecnología en momentos de campaña electoral - Criollo Burbano, Marcelo (2020)
This article analyzes two digital communicative strategies of LGBTI collectives during the 2017 electoral campaign in Ecuador. The discursive practices of subaltern audiences, their appropriation of technology and their political actions in the digital sphere are analyzed. Additionally, it includes the expression, style and discursive spaces that these audiences use to discuss their demands in digital platforms. An optimistic view considers that technology and digital networks have allowed an increase of forms of participation and greater visibility of LGBTI movements in Ecuador. From a less optimistic perspective, it is questioned whether these channels are adequate and sufficient for political participation and influence. Methodologically, we focus on the study of the forms of power of the statements. We ask ourselves: What topics are addressed and excluded from digital discourses? What strategies are put into play in these counterdiscourses? Finally, from the perspective of collective action, an approach is made about the complexities of the subordinate public and its emanci-patory potential in an electoral campaign context.